PENGEMBANGAN SISTEM PEMBAYARAN NON TUNAI MEMANFAATKAN TEKNOLOGI NEAR FIELD COMMUNICATION (NFC) - Harun Mukhtar; Efry Hady Nata; Desti Mualfah; Syahril Syahril; Rahmad Firdaus (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
The demands of rapid technology development test the need and necessity for implementation. Coercion of implementation seems to be happening in recent conditions, where the world is being hit by a virus that requires social distancing. Transaction processes that always interact with touch will be replaced by technology. Near-field Communication (NFC) which relies on magnetic technology has been designed on various objects as a means of connecting with financial data, making it easier for users to make transactions